A simple and sensitive sensor for lactose based on cascade reactions in Au nanoclusters and enzymes co-encapsulated metal-organic frameworks. (1st March 2021) - Guo, Manli; Chi, Jingtian; Zhang, Chi; Wang, Minglin; Liang, Hui; Hou, Juying; Ai, Shiyun; Li, Xiangyang
Highlights: AuNCs/enzymes co-embedded ZIF-8 was manufactured as a fluorescence lactose sensor. The composite was simply prepared using co-precipitation methods at room temperature. The introduce of Fe 2+ enhanced the quenching effects of the system. Quenching effects were enhanced by the ZIF-8 coating. Abstract: In this work, one kind of zeolite imidazole frameworks containing bovine serum albumin stabilized Au nanoclusters (AuNCs), β-galactosidase (β-Gal) and glucose oxidase (GOx) (AuNCs/β-Gal/GOx@ZIF-8) were obtained to detect lactose. Compared with other fluorescent nano-materials, AuNCs show distinct advantages as a guest species in ZIF-8, specifically their extremely small size (<1 nm), simple synthesis, excellent biocompatibility and high stability. Furthermore, the bovine serum albumin on their surfaces can promote the formation of ZIF-8 coating; thus, AuNCs were co-encapsulated in ZIF-8 with the enzymes together. X-ray diffraction (XRD) analysis indicates the composite possesses the similar crystalline structure with pure ZIF-8. Fluorescence microscope images, Fourier transform infrared spectra and energy dispersive X-ray spectroscopy indicate the presence of AuNCs in the composite. Owing to the high local concentrations of the fluorescent probe and the quenching agent in AuNCs/β-Gal/GOx@ZIF-8, the quenching rate was enhanced 3.4-fold that of free AuNCs and enzymes in solution.